2006
DOI: 10.1002/jcb.21052
|View full text |Cite
|
Sign up to set email alerts
|

Lamins of ocular lens epithelial cells

Abstract: Experiments were performed to characterize a prominent nuclear matrix (NM) protein isolated from tissue cultured mouse lens epithelial cells. This NM protein was separated by SDS-PAGE and the stained gel band was analyzed by mass spectroscopy. Blast analysis of the amino acid sequence derived by mass spectroscopy revealed the presence of Lamin C in the NM of the mouse lens epithelial cells. We also examined nuclear proteins of adult and fetal human lenses. Data collected from these experiments showed the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Heydari et al [1993] reported that the age related decline in HSP‐70 expression was caused at the transcriptional level, by decreased binding of HSF‐1 to the heat shock element of HSP‐70. The down regulation of hsp synthesis could also be modulated by alterations in the nuclear matrix organization initiated by changes in the aging Lamin‐C structure [Stein, 1993; Bagchi et al, 2007]. The lens epithelial cells (αTN‐4) used in these experiments were immortalized with introduction of α‐crystallin promoter fused with T‐antigen, thus these cells do not display proliferative senescence and an age related decrease of HSF‐1 activities.…”
Section: Discussionmentioning
confidence: 99%
“…Heydari et al [1993] reported that the age related decline in HSP‐70 expression was caused at the transcriptional level, by decreased binding of HSF‐1 to the heat shock element of HSP‐70. The down regulation of hsp synthesis could also be modulated by alterations in the nuclear matrix organization initiated by changes in the aging Lamin‐C structure [Stein, 1993; Bagchi et al, 2007]. The lens epithelial cells (αTN‐4) used in these experiments were immortalized with introduction of α‐crystallin promoter fused with T‐antigen, thus these cells do not display proliferative senescence and an age related decrease of HSF‐1 activities.…”
Section: Discussionmentioning
confidence: 99%
“…In 1997, Prusiner and collaborators won the Nobel Prize for the discovery of “Prions – a new biological principle of infection” and for their contribution on prion research development. While the consensus is that prion proteins (denoted PrP SC from Scrapie) are the causative agents of prion diseases, and further evidence support that PRNP —a host gene that regulates the expression of the prion protein PrP C —plays a crucial role in the development of TSEs,16 some researchers proposed bacterias17,18 and viruses19 as causative agents of TSEs. However, these theories were soon dismissed 20–22…”
Section: Introductionmentioning
confidence: 99%